Melanoma Patients’ Information Page – internet as support for patients and as tool for health education - Mackiewicz-Wysocka, Małgorzata; Grabarczyk, Piotr; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2000)
The internet service – Melanoma Patients’Information Page at www.mpip.org turned out to be a perfect informational and educational tool. Interactive tutorial on „how to spot melanoma”, automatic glossifier providing help in understanding medical articles and prognostic calculator for evaluation of probability of 10 years survival are examples of using internet for malignant melanoma prevention and for support for melanoma patients.